Pengaruh Budaya Organisasi dan Motivasi Kerja Terhadap Kinerja Melalui Kepuasan Kerja Pegawai Negeri Sipil (PNS) di Kantor Kecamatan Kota Waingapu Kabupaten Sumba Timur – NTT - Seprian Anthonius Linda; A. A. Rai Sita Laksmi; A.A.A. Dewi Larantika (Universitas Warmadewa, 2023)
This study aims to determine and analyze the influence of organizational culture on the performance of civil servants, the effect of work motivation on the performance of civil servants, the effect of job satisfaction on the performance of civil servants, the influence of organizational culture, work motivation and job satisfaction on the performance of civil servants, the influence of organizational culture and work motivation on job satisfaction, the influence of organizational culture on the performance of civil servants through job satisfaction, the effect of work motivation on the performance of civil servants through job satisfaction at the Waingapu City District Office. The research method used is quantitative using a questionnaire as a data collection material which was analyzed with the help of SPSS version 25 software. The population in this study amounted to 14 people, so the sampling method applied was saturated sampling (census). Data was collected by distributing questionnaires. The analytical method used is the path analysis method. The results showed that (1) organizational culture had no effect on the performance of civil servants; (2) work motivation has a significant effect on the performance of civil servants; (3) job satisfaction does not affect the performance of civil servants; (4) Organizational culture, work motivation and job satisfaction simultaneously have a significant effect on the performance of civil servants; (5) Organizational culture and motivation simultaneously have a significant effect on job satisfaction; (6) organizational culture has no significant effect on the performance of civil servants through job satisfaction; (7) Work motivation has no significant effect on employee performance through job satisfaction of civil servants.